Dynamics of changes in the concentration of heat shock protein (HSP70) in the cerebral cortex and hippocampus in experimental violation of cerebral circulation: the ability to regulate this process through positive modulation of thiol- disulfide system - Belenichev, I. F.; Gorbacheva, S. V.; Bukhtiyarova, N. V.; Levich, S. V.; Бєленічев, Ігор Федорович; Горбачова, Світлана Василівна; Бухтіярова, Ніна Вікторівна; Левіч, Сергій Вадимович (Bulgaria: Hikari Ltd, 2016)
Objective: Ischemic brain damage is the main factor of pathogenesis of various CNS disorders, which are observed in clinical practice. Nowadays, it is established that the parts of the brain are differ in their sensitivity to ischemia. It was noted that in the hippocampus and cerebellum, the proportion of necrotic neurons is significantly higher than in other cerebral structures. The goal of this research was estimation of possible pharmacological regulation of endogenous neuroprotective factor (HSP70 - heat shock protein) by the positive modulators of thiol-disulfide system in the neuronal cortex and hippocampus in the different periods after experimental cerebral vascular accident.
Keywords: Stroke; recovered glutathione; HSP70